Coping Strategies and Quality of Life of Children with Type 1 Diabetes Mellitus: A Preliminary Study. (29th March 2019) - Mulyasari, Rina; Agustini, Nur; Rustina, Yeni
ABSTRACT: This study was conducted to identify the correlations between the coping strategies and the quality of life of children with type 1 diabetes mellitus (T1DM). This cross-sectional study involved 39 children from 13 to 18 years old with T1DM who were selected using the consecutive sampling technique. The Pediatric Quality of Life Inventory 3.2 and Coping with a Disease questionnaire were used for this research, and the statistical analysis was conducted using the Pearson and Spearman correlation tests. The average age of the participants was 15.23 years old (± 1.81), they had been diagnosed with T1DM for an average of 5.54 years (± 3.06), and 59% were females. The most commonly used coping method was wishful thinking, and the quality of life mean was 63.82. The emotional reaction ( p  = 0.009, r = −0.413) and acceptance ( p  = 0.049. r = 0.317) coping strategies were significantly correlated with the quality of life. However, the other four coping strategies had no significant correlations with the quality of life. These study findings suggest that nurses should help to prevent children with T1DM from adopting emotional reactions as long-term coping mechanisms. Moreover, they should promote the use of the acceptance coping mechanism when providing nursing care for children with T1DM.